The Effect of Corporate Governance on The Tendency of Family Firms To Conduct Earnings Management Using WarpPLS - Dyah Febriantina Istiqomah (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Conflicts of interest that occur in family companies are not only conflicts between managers and owners, but ownership that is concentrated in the family tends to cause conflict between majority and minority owners. This conflict leads to opportunistic earnings management behavior. Earnings management behavior can be avoided by good corporate governance. Therefore, this study was conducted to determine the level of earnings management in family companies by considering the characteristics of corporate governance. This study uses 117 samples taken by purposive sampling of companies listed on the Indonesian stock exchange. The research method uses WarpPLS approach to examine the moderation effect. The results of the study show that there is no tendency for family companies to conduct earnings management. Likewise, the effect of moderating Corporate Governance on earnings management behavior is not proven. However, based on the results found the effect of Corporate Governance on earnings management behavior that shows the better corporate governance, seen from the proportion of independent commissioners, the number of audit committees, and audit quality, the lower earnings management practices in companies. The results of this study indicate a Predictor relationship where the moderating variable changes to an explanatory variable. This study are expected to open the company’s horizons about the importance of good corporate governance. In addition, for further research, more concerned with the level of involvement family members in the company because different levels, low, medium, or high, can influence the tendency of family members to do or not to do earnings management.